2022
DOI: 10.1532/hsf.4215
|View full text |Cite
|
Sign up to set email alerts
|

A Cardiac Surgery Mini-Elective Increases Specialty Knowledge Acquisition Among Pre-Clinical Medical Students

Abstract: Background: The introduction of integrated thoracic surgery residency programs has led to increased recruitment efforts of medical students to pursue a career in cardiac surgery. With little representation of cardiac surgery in medical school curriculum, we assessed a cardiac surgery mini-elective's efficacy in improving perceived knowledge among medical students. Methods: Preclinical medical students were offered the opportunity to participate in a cardiac surgery mini-elective, which consisted of five 2-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…One study used session-based surveys of common cardiac surgery topics like extra-corporal membrane oxygenation (ECMO) and cardiopulmonary bypass (CBP) to evaluate the effectiveness of cardiac surgery mini-elective sessions in improving undergraduates' knowledge about the specialty. The study found a significant improvement when comparing the results of pre- and post-session surveys [ 8 ]. The results of a similar study showed an 81% rise in interest in the field of cardiac surgery [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study used session-based surveys of common cardiac surgery topics like extra-corporal membrane oxygenation (ECMO) and cardiopulmonary bypass (CBP) to evaluate the effectiveness of cardiac surgery mini-elective sessions in improving undergraduates' knowledge about the specialty. The study found a significant improvement when comparing the results of pre- and post-session surveys [ 8 ]. The results of a similar study showed an 81% rise in interest in the field of cardiac surgery [ 3 ].…”
Section: Discussionmentioning
confidence: 99%